Carbon footprint assessment of a wood multi-residential building considering biogenic carbon. (10th June 2023) - Ouellet-Plamondon, Claudiane M.; Ramseier, Livia; Balouktsi, Maria; Delem, Laetitia; Foliente, Greg; Francart, Nicolas; Garcia-Martinez, Antonio; Hoxha, Endrit; Lützkendorf, Thomas; Nygaard Rasmussen, Freja; Peuportier, Bruno; Butler, Jarred; et al.
Abstract: Wood and other bio-based building materials are often perceived as a good choice from a climate mitigation perspective. This article compares the life cycle assessment of the same multi-residential building from the perspective of 16 countries participating in the international project Annex 72 of the International Energy Agency to determine the effects of different datasets and methods of accounting for biogenic carbon in wood construction. Three assessment methods are herein considered: two recognized in the standards (the so-called 0/0 method and −1/+1 method) and a variation of the latter (−1/+1* method) used in Australia, Canada, France, and New Zealand. The 0/0 method considers neither fixation in the production stage nor releases of biogenic carbon at the end of a wood product's life. In contrast, the −1/+1 method accounts for the fixation of biogenic carbon in the production stage and its release in the end-of-life stage, irrespective of the disposal scenario (recycling, incineration or landfill). The −1/+1 method assumes that landfills offer only a temporary sequestration of carbon. In the −1/+1* variation, landfills and recycling are considered a partly permanent sequestration of biogenic carbon and thus fewer emissions are accounted for in the end-of-life stage. We examine the variability of the calculated life cycle-based greenhouse gas emissions calculated for a case study building by each participating country, within the same assessment method and across the methods. The results vary substantially. The main reasons for deviations are whether or not landfills and recycling are considered a partly permanent sequestration of biogenic carbon and a mismatch in the biogenic carbon balance. Our findings support the need for further research and to develop practical guidelines to harmonize life cycle assessment methods of buildings with bio-based materials. Graphical abstract: Image 1 Highlights: Life cycle assessments of the same multi-residential building were carried out by experts from 16 countries. Effects of methods and datasets of biogenic carbon accounting in wood construction were identified. Different end-of-life scenarios (incineration, landfill, recycling) cause variations in the results. Different interpretations of the permanence of storing biogenic carbon in landfills also cause variations in the results. The input and output flows of biogenic carbon must be balanced to correctly assess its climate change impacts.